Pulmonary tuberculosis in gestational patient with diabetes mellitus in regional public hospital Dumai, Riau Province: a case report - Lestari, Marsita Ayu; Amir, Amrizal (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Diabetes mellitus increases the risk of pulmonary tuberculosis, whereas pulmonary tuberculosis can aggravate glycemic control. Pulmonary tuberculosis with diabetes mellitus in pregnancy is the complex problems to concern about maternal and fetal complications. We report a 38-year-old pregnant woman with a bloody cough for two days as a chief complaint-volume ± 400 millilitres in every cough. She also complained a chronic cough, dyspnea, fatigue and weight loss approximately eight kg in six months. Four months ago, she had a bloody cough one tablespoon. The patient was hospitalized. The patient also felt thirsty and urinate frequently, but she did not check the plasma glucose level. The patient had a baby with weight birth 4600 gram, her son 3 year-old received TB drugs and her sister with diabetes mellitus. In physical examination, pale conjunctiva, and crackles in the lower region of the right lung and all regions of the left lung. The results of laboratory are Hb 10.7 g/dL, monosit 11%, ESR 31%, fasting plasma glucose 137 mg/dl, A1C 7.3%, spot 3+ early morning 3+ spot 2+ (sputum). A chest x-ray showed an infiltrate in the field of the left lung. The patient had a pulmonary tuberculosis and diabetes mellitus in pregnancy. The patient was cared by internist, obstetrician and nutritionist.pulmonary tuberculosis and diabetes mellitus in pregnancy can increase morbidity of maternal and fetal. Evaluation of plasma glucose level was needed to determine diagnosis of type 2 diabetes mellitus or gestational diabetes. Integrated management of internist, obstetrician and nutritionist were needed to treat it.